Multimedia Video to Improve the Competence of Resuscitation Skills in Newborns: A Quasi-Experimental Study - Nelly Karlinah; Ani Triana; Berliana Irianti; Nur Israyati; Nurhapipa; Sandy Setiawati (Lembaga Publikasi Ilmiah Nusantara, 2026)
Neonatal mortality remains a global challenge, particularly in cases of neonatal asphyxia that require immediate and appropriate resuscitation management. Neonatal resuscitation competence is an essential skill for midwifery students. This study aimed to analyse the effectiveness of video-based multimedia learning in improving neonatal resuscitation competence among undergraduate midwifery students. A quasi-experimental pretest-posttest control group design was used involving 110 seventh-semester Midwifery students selected through purposive sampling. Participants were divided into and intervention groups (n=55) that received video-based learning and a control group (n=55) that received conventional lecturing. Students' understanding was assessed using questionnaires, while resuscitation skills were evaluated using OSCE observation sheets. Data were analysed using an independent sample t-test with a significance level of p<0.05. The results showed significant improvement in students’ understanding scores, from 52.65 to 85.98 (p<0.001), while practical resuscitation competence increased from 18.2% to 81.8% after the intervention. Video-based multimedia learning was effective in improving neonatal resuscitation competence and may serve as an innovative learning strategy to support neonatal emergency preparedness among students.